Study of some biochemical parameters in patients Of acute myeloid leukemia - Haethem Qassim Mohammed (College of Pharmacy / Mustansiriyah University, 2007)
Hundred and fifty samples were collected patients with acute myeloid leukemia in the national center of Hematology, from period began at (1) June till end of December 2004. The diagnosis of acute myeloid leukemia was made according to standard hematological criteria. Twenty five patients had (France, American, British) type M2 before treatment chemotherapy and 25 patients after chemotherapy, and leukemia patients M4 before treatment Average age of patient is 36.6 years and sex is 64% males and 36% females The study calculated the renal function by measuring urea and creatinine 40% of patients have elevated urea , 42% have elevation in creatinine either after or before treatment as possible complication of leukemia Introduction Leukemia means a group of disorders characterized by the accumulation of abnormal cells which may cause bone marrow failure Raised circulating white cells count and infiltrate other organs Acute Myelogenous Leukemia (AML) called granulocytic or myelocytic leukemia account for about 20% of childhood leukemia (2). AML is a cancer of bone marrow which characterized by granulocytic cells predominance, these a typical blood cells are produced in the bone marrow.